FROM DATA TO CLAIM: UNDERSTANDING THE WARRANT DEFICIT IN INDONESIAN UNDERGRADUATE ACADEMIC WRITING - Muthmainnah Mursidin; Sitti Nurjannah (e-Journal of ELTS (English Language Teaching Society), 2026)
Constructing logical warrants to connect factual evidence with interpretive claims represents a core yet widely underemphasized writing skill among university students. This investigation examines why EFL undergraduates at an Indonesian university encounter persistent difficulties in warrant-based argumentation and how such difficulties constrain the growth of their higher-order thinking capacities. A descriptive qualitative approach guided data collection from 20 students at Universitas Islam Makassar, South Sulawesi, using three complementary instruments: a critical-thinking writing assessment, a timed argumentative composition task, and semi-structured interviews. Student outputs were coded and evaluated through the lens of Toulmin’s Argumentation Model (2021), with particular attention to the logical bridges students constructed—or failed to construct—between their evidence and their conclusions. Results expose a striking “Synthesis Crisis”: although the overwhelming majority of students (85%) showed competence in distinguishing facts from opinions at the sentence level, a mere 10% succeeded in weaving these elements into warranted arguments within extended writing. The investigation pinpoints three intertwined barriers: (1) an evidence-accumulation strategy devoid of interpretive purpose, exhibited in 35% of written outputs; (2) a pervasive equation of academic stance with subjective personal feeling, documented among 60% of respondents; and (3) a near-total failure to articulate logical warrants, observed in 80% of all essays examined. The study concludes that prevailing EFL writing pedagogy in Indonesian tertiary institutions—preoccupied with correctness and structure—falls critically short of fostering genuine argumentative competence. Curricular reform centered on warrant-explicit instruction is urgently warranted.